THE THOUGHT MANIFESTATION FREEDOM AND THE RIGHT TO INFORMATION AS PERSONALITY RIGHTS AND FUNDAMENTAL RIGHTS (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
This paper main purpose is to demonstrate that the right to the thoughts free expression, connected to the right to expression freedom, is the right provided for in art. 5º, IV of the Federal Constitution. It also intends to analyze the conflict among constitutional laws and its resolution through hermeneutics and ponderation. The real case concerning the sealing of books in the “Bienal do Rio de Janeiro” was used as an example of a court decision involving a law conflict and, in this particular case, the conflict between the right of thought information freedom and the right to information. The research method used was the hypothetical deductive, aside to the legislation, doctrinal bibliographic materials and, mainly, the jurisprudence, that have been used as instrumental procedures.